Improving the mechanical properties of carbon nanotubes reinforced aluminum matrix composites by heterogeneous structural design. (January 2022) - Xu, Z.Y.; Li, C.J.; Gao, P.; You, X.; Bao, R.; Fang, D.; Tao, J.M.; Yi, J.H.
Abstract: A novel aluminum matrix composites with different lengths of CNTs and heterogeneous structural were prepared in this paper. The synergistic effect of reinforcements with different lengths improves the mechanical properties of composites. Meanwhile, the heterogeneous structure design introduced fiber-like reinforcement to enhance the strength and toughness of composite. Graphical abstract: Image 1 Highlights: Heterogeneous structures achieve a balance between strength and ductility. The synergy of CNTs with different lengths is brought into full play. The strengthening and toughening mechanism of the composites was explored.